Students' and lecturers' conceptions and philosophy of teaching and learning in university - Abu, Baharin (Penerbit UTM Press, 2001)
This paper examines students' and lecturers' conceptions and philosophy of university teaching and learning at the Universiti Teknologi Malaysia Johor. The study extends the earlier work by Taylor (1983) and Saljo (1979) and other study series by Entwistle, Mart on and their colleagues in the Western culture whereas several other works in Eastern cultures especially headed by Biggs. Watkins & Regmi, Kember & Gow and others. However, there is no such work done, recorded or extended in Malaysia. This study employs a combination of phenomenography inquiry (see Marton & Saljo , 1984; Svensson, 1985; Saljo, 1988) and quahtan vc paradigm (see Burgess, 1984a ,b; Bryman . 1988 ; Milcs & Huberman, 1994 ; Patton, 19 80, 1987; Merriam 1988) with in-depth exploratory, descriptive and analytical character istics (Yin, 1994; Stake, 1980 , 1995). Data from interviews were gathered from students from diffe rent years of study and different levels of academic staff members. The analysis was then carried out on the relevant parts of the verbatim transcripts of the interview which are subjected to two stage analysis. First, the findings are analyzed according to what emerged as the key research issue from the three original questions to answer conceptions and philosophy of university education and its teachin g and learning activities. Second, adopting the phenomenographic approach, expressions reflecting conceptions of learning were identified and grouped on the basis of similarities, differences and complementarities (Marton et al., 1993) and they are then organized according to both lecturers' and students' conceptions and philosophy of teaching and learning, respectively. The findings revealed that some qualitatively different conceptions of teaching and learning in Malaysia were similar to the Western findings and the philosophy held concorded to the international goals of higher education. However, further differentiantions have also been made within the various conceptions and some significant differences have been acknowledged which are due to 'soft' moral-cultural and strong religion influences. Conclusively the conceptions. philosophy and aims of university education in Malaysia are seen indirectly orientated to one major theme that is, 10 satisfy national political and economic orientations that may present conflicts in the system.